Alternations of Cell-Cycle Regulators in Localized Synovial Sarcoma- a Multifactorial Study with Prognostic Implications - Antonescu, C. (Institutional Knowledge at Singapore Management University, 2000)
Genetic alterations of cell cycle regulators are thought to represent uncommon and possible secondary events in sarcomas characterized by recurrent chromosomal translocations. The present study investigates this hypothesis on synovial sarcoma (SS), assessing the frequency of expression and possible clinical implications of detecting alterations in critical cell cycle regulatory proteins. A homogeneous cohort of 49 patients with localized SS, restricted to the extremity and with available long-term follow-up information, was selected from our files. We focused our study on molecules involved in the G1 checkpoint and G1-S transition, including cyclins D1 and E, p21WAF1, p27Kip1, mdm2, p53, and Ki67. A cutoff point of 10% immunoreactive tumor cell nuclei was selected to define a positive phenotype for any given marker, except for Ki67. High Ki67 proliferative index was considered when ?20% tumor cells displayed nuclear immunoreactivity. Biphasic SS were analyzed, taking into account separately the expression of these proteins in the spindle and glandular components. Disease specific survival was modeled using the Kaplan-Meier method with log rank test and Cox regression. The cohort of patients analyzed included 23 females and 26 males, and the histological type distribution was 35 monophasic and 14 biphasic SS. The median follow-up for survivors was 53 months, with a 5-year disease-specific survival of 63% and a metastatic disease-free survival of 40%. The positive phenotypes identified for the different markers studied were as follows: cyclin D1, 59%; cyclin E, 29%; p21, 51%; p27, 69%; mdm2, 59%; p53, 16%; and Ki67, 59%. We observed that positive p53, cyclin E, and high Ki67 proliferative index were correlated with survival, but only Ki67 and p53 were independent variables for prognostication. The present study suggests that alterations of cell cycle regulators are more common events in SS than originally thought. p53 overexpression could be of use as a marker together with a high Ki67 proliferative index, in identifying a subset of SS patients with increased risk of tumor relapse.